USING SYNECTIC STRATEGY TO IMPROVE THE STUDENT’S VOCABULARY - Musni, Nurul Fatanah; Munir, Munir; Fitri, Nur (State University of Makassar, 2022)
The aim of this study is to improve learners' vocabulary ability. through Synectic strategies. pre-experimental design is the method used by researchers with one group pre-test and post-test. The population in this study were students of class X MAN 1 Barru in the academic year 2022/2023. Cluster random sampling is used in this research. in this case, the researcher chose class X MIA 1 as a representation of the population consisting of 26 students. The results of this study prove that there is a significant difference between students' scores before treatment and students' scores after treatment are evident from the students' pre-test normal scores (56,88) and should be lower than the post-test means (87,04). In addition, by using a Synectic strategy, students can remember words, train students’ creativity, and are effective in teaching vocabulary at MAN 1 Barru Keywords— Synectic Strategy and improve Vocabulary